Victim impact statements limit the effects of perspective taking on juror decisions - Skorinko, Jeanine Lee McHugh; Laurent, Sean; Bendremer, Emily; Schneider, Kaitlyn; Hale, Valicia; Iannacchione, Alisionna; Paris, Melissa; Demircioglu, Gizem; Wesley, Kyla; LaValley, Julia; DeFreitas, Angelica; Blumenthal, Jeremy (Frontiers in Cognition, 2024)
Past work suggests that victim impact statements (VISs) encourage jurors to take victims' perspectives, but this has not been explored empirically. Across four experiments (total N = 881), the present research examines the effects of perspective taking and the impact of the crime expressed in VISs on juror perceptions of defendants. In Experiment 1, mock jurors read a capital murder case that prompted them to perspective take (or not) and included VISs that were high or low in impact of the crime on the victims. Results indicate that the impact of the crime expressed in the VISs influenced perceptions of culpability for the defendant, but perspective taking did not. Experiment 2 used an armed robbery case, and the results again showed that the higher impact of the VIS led to seeing the defendant as more culpable, but perspective taking did not. Experiment 3 examined whether the type of perspective taking mattered (imagining self vs. defendant) when VISs were also presented. Those using the self during perspective taking found the defendant less culpable compared to non-perspective takers. Experiment 4 examined whether priming perspective taking influenced decisions. While high-impact VISs resulted in more death penalty sentences than low-impact VISs, priming perspective taking did not. Overall, the impact of the crime expressed in VIS typically influenced the perceptions of the defendants. In contrast, perspective taking had limited effects. These findings contribute to our understanding of VISs in the courtroom and may be useful for attorneys when presenting cases and advising clients.